2009
DOI: 10.1016/j.jtcvs.2008.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Re-creation of a sinuslike graft expansion in Bentall procedure reduces stress at the coronary button anastomoses: A finite element study

Abstract: Even though finite elements technique is necessarily a simplification of a real biologic environment, all tests seem to indicate that a standard tubular graft gives a higher stress to coronary sutures. Relieving the stress on the coronary anastomoses by using a graft with preformed sinuses of Valsalva may decrease the incidence of postoperative complications such as bleeding and late pseudoaneurysm formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 17 publications
(17 reference statements)
0
23
0
Order By: Relevance
“…In this manner, the PEARS allows the aorta to expand and recoil without the risk of dilatation. The PTFE mesh used to manufacture the PEARS is approximately 2.6 times stiffer than the Marfan aortic wall [24,25]. The material itself is less stiff than the material generally used (Haemashield, Dacron) to perform the Bentall or valve-sparing root replacements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this manner, the PEARS allows the aorta to expand and recoil without the risk of dilatation. The PTFE mesh used to manufacture the PEARS is approximately 2.6 times stiffer than the Marfan aortic wall [24,25]. The material itself is less stiff than the material generally used (Haemashield, Dacron) to perform the Bentall or valve-sparing root replacements.…”
Section: Discussionmentioning
confidence: 99%
“…The elastic moduli of the aortic wall and PEARS were obtained from previously reported experimental data [24,25]. Based on the sheep study by Verbrugghe et al [14], the composite "wall-PEARS" showed approximately 125% increase in stiffness compared with the non-wrapped artery.…”
Section: Fe Modelling Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…This routinely performed procedure provides a better annular stabilization combined with a superior support of the aortic wall. On the other hand, the root looses any extensibility at all levels [48], because of the material with different elastic characteristics (more rigid) with respect to the native aorta. Recently, a novel Dacron conduit that allows the reconstruction of pseudo-sinuses of Valsalva has been proposed by De Paulis et al [13], even if this prosthesis does not reproduce three independent sinuses, but rather a single axisymmetric bulb.…”
mentioning
confidence: 99%
“…In surgery, the two coronaries, previously separated, need to be reconnected to the aortic root wall, as close as possible to their natural position. This procedure may have intra-operative (bleeding) and postoperative (bleeding and late pseudo-aneurysm formation) complications due to the high torsion or tension at the level of the coronary-root anastomoses: the introduction of valved Dacron conduits has simplified and expedited the surgical procedure, with reduced complications when compared with the remodeling technique [48]. The natural trilobed geometry of the aortic root is commonly associated to ensuring the proper opening of the natural aortic valve that has three leaflets opening to the wall in correspondence of the three sinuses.…”
mentioning
confidence: 99%